Phytolith occluded organic carbon in Fagopyrum (Polygonaceae) plants: Insights on the carbon sink potential of cultivated buckwheat planting - Wang, Linjiao; Sheng, Maoyin (Frontiers in Plant Science, 2022)
Crop cultivation has a great potential of phytolith carbon sink and can play important roles in the long-term stable carbon sequestration of terrestrial ecosystems. Buckwheat, an important multigrain crop with very long cultivation history, is widely planting around world. Phytolith carbon sink potential of buckwheat planting is still limited in the in-depth understanding of biogeochemical carbon sequestration in croplands. In order to estimate the phytolith carbon sink potential of buckwheat planting, in the present study, six species including seventeen populations of Fagopyrum plants were selected as study materials. Firstly, their phytoliths were extracted by the wet oxidation method; then the PhytOC (phytolith occluded organic carbon) contents were determined by spectrophotometry method; finally, phytolith carbon sink potential of buckwheat planting was estimated. Results showed: 1) PhytOC content range of the six Fagopyrum species studied was 0.006% ~ 0.038%, which were significantly lower than that of rice, wheat, sugarcane, and some cereal and oil crops. There were significant differences in total silicon, phytolith and PhytOC content of Fagopyrum plants among different species, different organs (root, stem and leaf), and different living forms (annual, partly perennial and completely perennial). There were significant positive relationships between PhytOC and phytolith content, and between phytolith and total silicon content. 2) Average phytolith carbon sequestration rate of F. esculentum and F. tataricum planting was 2.62 × 10-3 and 1.17 × 10-3 t CO2 hm-2•a-1, respectively, being approximately equal to that of terrestrial shrub vegetation. 3) The global total amount of phytolith carbon sequestration of buckwheat planting reached 5102.09 t CO2 in 2018, and the Chinese total amount of phytolith carbon sequestration of buckwheat cultivation was 624.79 t CO2 in 2020. Phytolith carbon sink of buckwheat planting had a significant potential for playing obvious roles in carbon cycle. The present results are of great significances in crop phytolith studies and provide important references for phytolith carbon sink potential estimation of farmland ecosystems.